Asuhan Kebidanan Komprehensif Ny “S” dengan Anemia Ringan di Puskesmas Pangale Kabupaten Mamuju Tengah - Mahmud, Abbas; Nurdiana, Nurdiana; Ulandari, Ratni (Jurnal Kebidanan Malakbi, 2020)
Anemia in pregnancy is a national problem because it reflects the value of the socioeconomic welfare of the community, and its influence is very large on the quality of human resources. Pregnancy anemia is called "potential danger to mother and child", therefore anemia requires serious attention from all parties involved in health care at the forefront. Provide comprehensive midwifery care starting from pregnancy, maternity, LBW, postpartum, neonatal and family planning care. Using descriptive method with a case study approach. Case studies were conducted using primary and secondary data collection techniques. Primary data include interviews, observations and physical examinations as well as care, while secondary data includes excavation of data in the cohort of research subjects, data from the MCH book. The results of care are analyzed by comparing theories with the cases determined using the SOAP care approach. Mrs "S" GIP0A0, age 20 years, gestational age 33 weeks 5 days Lab results: HB 10 g / dl. Care was given for 3 visits to Mrs. Hb. S. The results of visits to Mrs. "S" during the third trimester of pregnancy there are no complications, spontaneous labor in delivery, presentation back of the head, decrease hodge 0/5 without complications, in the puerperium with normal puerperium, in BBL with BBLN, in neonatal with physiological and on family planning, you want to become an injectable family planning acceptor. From comprehensive midwifery care in Mrs. "S" who experienced mild anemia, no complications were found ranging from pregnancy, childbirth, LBW, postpartum neonates and family planning.